PEMILIHAN WALI NAGARI DALAM SISTEM PEMERINTAHAN DAERAH DI KABUPATEN PADANG PARIMAN - Putri, Rianda Prima (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
The granting of authority to local governments to administer their government is carried out through a process called. decentralization to autonomous regions or known as regional autonomy. Decentralization has two forms, namely political and administrative. Political decentralization, namely the authority to make decisions and exercise certain control over resources given to local and regional governments. Administrative decentralization is a delegation of implementing authority given to central officials at the local level. Its powers range from setting regulations to substantial decisions. The holding of the simultaneous election of nagari guardians in Padang Pariaman Regency in 2018 has not gone well from the 41 Nagari who held the pilwana. The stages that are passed in the holding of the Nagari mayoral election are: preparation, nomination, voting, and determination that has been running according to the rules. It's just that there is one election dispute that occurred in Nagari Guguak District 2x11 Kayutanam. In holding the simultaneous election of nagari guardians in Padang Pariaman Regency in 2018 only in Nagari Guguak, 2x11 Kayutanam District.